From clearing to cerradão: the impact of seedling planting on the ecological restoration of the Cerrado - Bertti, Mariana Cióca; Weiser, Veridiana de Lara (Technical and Scientific Journal Green Cities, 2025)
Brazil, recognized for its biodiversity, hosts about 10% of the world's species, with the Cerrado biome standing out as the richest savanna in diversity. However, this biome faces serious challenges, such as the conversion of native vegetation for human use, resulting in an alarming deforestation rate. Despite this degradation, the recovery of Cerrado ecosystems is possible through natural regeneration and ecological restoration, which involves the introduction of native seedlings through planting. This study characterizes the community of plant species in an ecological restoration area, with different types of treatment, after 23 years of planting. We sampled 626 individuals from 71 species, of which 64 are native regenerants. The results show that soil coverage reached 85.1%, and the density of individuals was 3,792 per hectare, indicating a process of floristic recomposition. The plots with invasive grass management and enrichment showed better results compared to untreated ones. These findings emphasize the importance of integrated management and restoration strategies for the successful recovery of native vegetation and the preservation of biodiversity in the Cerrado.
Keywords: Biodiversity; Native species; Floristic recomposition